Enhancing Students’ Vocabulary Achievement through Flashcards Strategy at Public Elementary School - adhania, rifa (Universitas Maritim Raja Ali Haji (UMRAH), 2025)
This study investigated the effectiveness of flashcards in enhancing vocabulary achievement among third-grade students in a public elementary school in South Tangerang. A quantitative quasi-experimental design was applied, involving 33 students in the experimental group who received seven sessions of flashcard-based instruction and 32 students in the control group who received conventional teaching. Both groups completed pre-tests at the beginning and post-tests at the end of the intervention, and data were analyzed using SPSS. Analyses included descriptive statistics, item mastery, normality and homogeneity tests, N-gain calculation, and paired and independent t-tests. Results showed the experimental group achieved a mean post-test score of 16.88 (SD = 2.247), significantly higher than the control group’s 11.53 (SD = 1.951), with a mean difference of 5.35 points (t(63) = 10.233, p < 0.001). N-Gain analysis indicated a high gain of 0.70 (70.16%) for the experimental group, compared to 0.13 (12.80%) for the control group. Item-level analysis confirmed flashcards improved both recognition and productive use of vocabulary. Additionally, flashcards enhanced students’ motivation, engagement, and confidence through visual cues and interactive practice. The findings suggest flashcards are an effective, low-cost strategy for elementary EFL classrooms, guiding teachers in using engaging and multimodal tools.